2023
DOI: 10.1186/s40813-023-00303-3
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of an artificial intelligence system for estrus detection in sows

Abstract: Background Good estrus detection in sows is essential to predict the best moment of insemination. Nowadays, a technological innovation is available that detects the estrus of the sow via connected sensors and cameras. The collected data are subsequently analyzed by an artificial intelligence (AI) system. This study investigated whether such an AI system could support the farmer in optimizing the moment of insemination and reproductive performance. M&M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Those field experiments found that estrus signs can be detected about 10-20 h earlier by the SSB system than by manual systems. They concluded by stating the use of SSB improves farrowing rate and litter size and decreases repeat breeding rate [27].…”
Section: Artificial Intelligence and Machine Learning Models In Estru...mentioning
confidence: 99%
See 1 more Smart Citation
“…Those field experiments found that estrus signs can be detected about 10-20 h earlier by the SSB system than by manual systems. They concluded by stating the use of SSB improves farrowing rate and litter size and decreases repeat breeding rate [27].…”
Section: Artificial Intelligence and Machine Learning Models In Estru...mentioning
confidence: 99%
“…The average duration of a sow's estrous cycle is 21 days, which may vary from 17 to 25 days depending on breed and individual differences [26]. The standing heat is variable, lasting from 24 to 96 h, and the average duration is 40 to 60 h [15,27]. Once two-thirds of estrus has passed, ovulation takes place [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged and apparent estrus expression is vital for timely insemination, while concealed or less apparent estrus expression leads a lower conception rate [ 3 ]. Additionally, the absence of estrus expression results in the culling of a significant number of gilts from the breeding herd, posing one of the major unresolved challenges in the pig farming industry [ 4 ]. During estrus, female pigs exhibit various signs, including vaginal mucus secretion, vulva reddening, and swelling, indicating ovulation and readiness for mating [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%